Magnetic phenomena in Co-containing layered double hydroxides - Vieira, Daniel E.L.; Lopes, Augusto B.; Feher, Alexander; Čižmár, Erik; Babkin, Roman Yu.; Desnenko, Vladimir A.; Fertman, Elena L.; Pashkevich, Yurii G.; Fedorchenko, Alexey V.; Salak, Andrei N.; Ferreira, Mário G.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Magnetic behavior of CoII(n)AlIII layered double hydroxides (LDHs) (n = Co/Al = 2 and 3) intercalated withnitrate was studied as a function of temperature. Both LDH compounds are paramagnetic above about 8 K. A rapid increase of their magnetic moments occurs below this temperature until the moments reach the maximum values at Tmax of 4.0 K and 3.2 K for Co(2)Al–NO3 and Co(3)Al–NO3, respectively. Below Tmax, the zero-field-cooled and the field-cooled static magnetization curves are strongly different. Along with this low-temperature phenomena, Co(2)Al–NO3 and Co(3)Al–NO3 demonstrate anomalous behavior of their temperature dependence magnetic susceptibility in a higher-temperature range: between 75 and 175 K, both the paramagnetic Curie temperature and the effective magnetic moment change in a non-monotonous way. Possible structural reasons of the observed magnetic behavior of the CoII(n)AlIII LDHs are discussed.